Comparison of Penile Appearance and Outcomes Between Prefabricated Urethra and Pre-implanted Urethral Plate for Treatment of Children With Severe Hypospadias: A Retrospective Study - Ding, Yuan; Gu, Shengli; Xia, Xingrong; Yu, Zhengbo (Frontiers in Pediatrics, 2021)
Objective: To compare the effect of prefabricated urethra and pre-implanted urethral plate in the treatment of severe hypospadias in children. Methods: We retrospectively analyzed the clinical data of 53 patients who diagnosed as severe hypospadias underwent staging urethroplasty from January 2015 to January 2018 in the Department of Pediatric Surgery, First People's Hospital, Zunyi City. The patients were divided into two groups: group A (n=25) were treated with prefabricated urethra and group B (n=28) were treated with pre-implanted urethral plate. After the second stage surgery, the ratios of complications such as urethral fistula, urethral stenosis, urethrocele, and recurrence chordee were compared. The penis was scored from meatus, glans, shaft skin, general appearance by the parents, blinded urologists according to The Pediatric Penile Perception Score, and the scores were compared too. Results: All patients were followed up after two stage operations for an average of 28 months. Glans dehiscence occurred in two patients (8%), urethral orifice stenosis occurred in one (4%) and urethral fistula occurred in three (12%) in group A. No urethral stenosis, urethrocele and recurrence chordee was observed. One patient presented urethral plate inactivation (3.6%), two patients presented urethral fistula (7.1%) and one patient presented urethral stenosis (3.6%) in group B. No urethrocele, glans dehiscence and recurrence chordee was observed. The total complication rate in group A was 24% and 14.3% in group B, respectively, and the difference was not statistically significant (P = 0.582). The differences between two groups scored by parents in glans (P=0.030) was statistically significant. The differences between two groups scored by operators in meatus (P=0.041), shaft skin (P=0.000), glans (P=0.001) and general appearance (P=0.007) were statistically significant. The differences between two groups scored by counterparts in meatus (P=0.006), shaft skin (P=0.003), glans (P=0.010) and general appearance (P=0.014) were statistically significant. Conclusion: Both prefabricated urethra and pre-implanted urethral plate methods are suitable for correction of severe hypospadias as staging surgery in children. In general, pre-implanted urethral plate is more worthy of spread because it is much more applied in patients with small glans and achieve good appearance of penis.